Análisis automático morfológico con las herramientas Smorph y Nooj - Beltrán, Celina (2013)
Morphology has had a great development within the scope of Computational Linguistics since it is the starting point to accomplish researches in other levels of representation. This time our focus of attention is on N (nouns) and A (adjectives) and the working logic of each tool while its common characteristics and peculiarities are indicated. The operations that can be performed using SMORPH are subtraction and concatenation at the end of a string, so, to formalize names we deal with lemmas and terminations. NooJ shares with Smorph the use of subtraction and concatenation at the end of a string, but besides that Nooj acts on different places within words –at the beginning or at the end- to be determined by the user who has the possibility to point out the direction, leftward or rightward. Nooj also can change o duplicate characters. To construct morphological grammars and NooJ dictionaries we resort to the already organized INFOSUR Dictionary (entries).